ZAMAN AKHIR ORDE BARU DAN PERUBAHAN SUARA LOKAL DALAM SASTRA INDONESIA - Michael Bodden (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2005)
The conscious pattern of most Indonesian literary works presents a portrait of local culture as a conservative "tradition " that stands in the way of free and natural individual development, and may even bring about suffering and death. Modernization, or al least, modern individuals, are often portrayed in more positve ways, especially in the novels produced in the 7Os and 80s that carry local colors. Although the trend deviates in terms of apprecialion to individualism from the New Order ideology and practice, which worships technological and economic modernization yel is hostile to individualism and the ideology of democracy as characteristics of modernization not suitable with “kepribadian nasional modern"- from the perspective of commitment to modernization understood as “negara kesatuan” such a negative view by the national literature towards local culture is nonetheless in line wilh the government goals. This parallel view is also apparent in the centralized view of national culture in Jakarta from 1965 to 1985.Kata kunci: sastra nasional, warna daerah, warna lokal, identitas, budaya tradisional, modernisme.